PENGARUH OPINI AUDIT DAN TEMUAN AUDIT TERHADAP TINGKAT KORUPSI (STUDI PADA PEMERINTAH DAERAH DI INDONESIA TAHUN 2017) - Riri Safira Syahrir; Elly Suryani (JAF (Journal of Accounting and Finance), 2020)
This study aims to investigate the effect of audit opinion and audit findings on the level of corruption in the Regional Government in Indonesia in 2017. The object in this study is the local government included in the Public Integrity Survey conducted by the Corruption Eradication Commission in 2017. The sampling technique used in this study was saturated sampling with a total sample of 19 local government institutions. The method used in this analysis is multiple linear regression using IBM SPSS 25. Based on the results of the test the significance of audit opinions and audit findings simultaneously evaluating the level of corruption. Partially, audit opinion variables and negative audit findings on the level of corruption